2016
DOI: 10.1080/21645515.2016.1205769
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of mathematical models exploring the epidemiological impact of future TB vaccines

Abstract: Mathematical models are useful for assessing the potential epidemiological impact of future tuberculosis (TB) vaccines. We conducted a systematic review of mathematical models estimating the epidemiological impact of future human TB vaccines. PubMed, Embase and WHO Global Health Library were searched, 3-stage manual sifted, and citation- and reference-tracked, identifying 23 papers. An adapted quality assessment tool was developed, with a resulting median study quality score of 20/28. The literature remains di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 28 publications
(121 reference statements)
3
111
0
Order By: Relevance
“…Mathematical modelling provides a systematic framework to explore the potential future impact of vaccine characteristics and implementation strategies to inform target product profile development. The impact achieved might vary by epidemiological and demographic setting, 12,13 therefore country-specific models are needed for appropriate vaccine selection and implementation planning, including age targeting. A phase 3 clinical trial of a prophylactic tuberculosis vaccine candidate has been conducted in China (NCT01979900) and therefore, modelling to clarify the potential benefit of new tuberculosis vaccines and different implementation strategies in China is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modelling provides a systematic framework to explore the potential future impact of vaccine characteristics and implementation strategies to inform target product profile development. The impact achieved might vary by epidemiological and demographic setting, 12,13 therefore country-specific models are needed for appropriate vaccine selection and implementation planning, including age targeting. A phase 3 clinical trial of a prophylactic tuberculosis vaccine candidate has been conducted in China (NCT01979900) and therefore, modelling to clarify the potential benefit of new tuberculosis vaccines and different implementation strategies in China is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The strategies are based on distinct technical approaches, operating under the assumption that one approach is not necessarily better than another in light of the fact that a licensed vaccine against pulmonary TB still does not exist. A recent systematic review of publications attempting to mathematically model the epidemiological impact of future vaccines against TB designed to prevent infection, prevent disease, or both concluded that a new TB vaccine would be cost-effective (from both a health system and societal perspective), even in the context of a protection index as low as 20%, especially if delivered to adolescents and adults [47]. …”
Section: Resultsmentioning
confidence: 99%
“…For example, mass vaccination of adults using a new TB vaccine with only 40% efficacy would achieve the same initial reduction in TB incidence 20 years earlier than an infant vaccine with 80% efficacy and lifelong protection (Knight et al, 2014). Developing a new vaccine for use in mass campaigns to prevent pulmonary TB among adolescents and adults will be necessary to interrupt the cycle of Mtb transmission in the short-and medium-term (Knight et al, 2014), whereas some combination of infant and adolescent/adult vaccination approaches would likely be optimal to sustain long-term TB control (Harris et al, 2016).…”
Section: Target Populations For a New Tuberculosis Vaccinementioning
confidence: 99%
“…It is likely that future TB vaccination programs would use age-targeting to tailor routine vaccination schedules and mass campaigns for either Mtb-uninfected infants, children, and preadolescents in a pre-exposure strategy, or for Mtb-infected adolescents and adults in a post-exposure strategy, to maximize cost-effectiveness (Harris et al, 2016). However, the feasibility and efficiency of age-targeted vaccination would likely differ by country, depending on age-specific prevalence of Mtb infection and TB disease, which varies widely even in high TB burden countries.…”
Section: Target Populations For a New Tuberculosis Vaccinementioning
confidence: 99%